Waiting out the War on the Shore of Lake Superior: Camp 100 and Neys Provincial Park - O’Hagan, Michael (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
More than 2,000 combatant POWs, EMS, and Civilian Internees were interned at Camp 100 in Neys Ontario during the Second World War. Camp 100 evolved as the war progressed and as the Department of National Defence adapted its internment operations. The camp was established to simply hold POWs until the end of the war, but over the years, continued to improve its facilities and, eventually, provided prisoners with an array of recreational and educational opportunities to both keep themselves occupied and help prepare themselves for post-war life. The camp was one of the few to hold combatant POWs, EMS, civilian internees, and Japanese-Canadian internees. It therefore provides an excellent case study for Canada’s attempt to treat POWs humanely. The camp’s final wartime stage as a “Black” camp reveals how Canada attempted to solve the problem of what to do with its thousands of pro-Nazi POWs. Although re-education measures were met with varied success, they were the beginnings of converting former enemies into future allies.